2020
DOI: 10.1159/000511011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum and Outcomes of Ocular and Periocular Complications following External-Beam Radiotherapy for Inoperable Malignant Maxillary Sinus Tumors

Abstract: <b><i>Purpose:</i></b> To highlight the clinical spectrum, management, and outcomes of ocular/periocular complications following high-dose external-beam radiotherapy (EBRT) for inoperable malignant maxillary sinus-involving tumors (MMST). <b><i>Methods:</i></b> A retrospective, interventional case series. All patients who were diagnosed with inoperable MMST (with orbital involvement) and treated with high-dose fractionated EBRT (65 Gy in 30 fractions) at James Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Additionally, we showed that corneal healing was negatively affected by older age, larger infiltrate size and poorer presenting vision. Gaining a better knowledge of these prognostic factors may enable earlier interventions (e.g., temporary tarsorrhaphy or amniotic membrane transplant) to help promote corneal healing and re-epithelialisation (32)(33)(34)(35). The poorer corneal wound healing in older patients with BK is likely related to the presence of co-existing ocular surface diseases (e.g., dry eyes, neurotrophic keratopathy, and others), immunosuppression and the age-related reduction in proliferative ability of the limbal stem cells (36)(37)(38).…”
Section: Outcomes and Prognostic Factorsmentioning
confidence: 99%
“…Additionally, we showed that corneal healing was negatively affected by older age, larger infiltrate size and poorer presenting vision. Gaining a better knowledge of these prognostic factors may enable earlier interventions (e.g., temporary tarsorrhaphy or amniotic membrane transplant) to help promote corneal healing and re-epithelialisation (32)(33)(34)(35). The poorer corneal wound healing in older patients with BK is likely related to the presence of co-existing ocular surface diseases (e.g., dry eyes, neurotrophic keratopathy, and others), immunosuppression and the age-related reduction in proliferative ability of the limbal stem cells (36)(37)(38).…”
Section: Outcomes and Prognostic Factorsmentioning
confidence: 99%
“…Its management and accurate diagnosis are challenging due to the diverse underlying ocular and systemic diseases such as dry eye, tear film alteration, limbal stem cell dysfunction, corneal dystrophies, chronic use of topical medications, herpetic infection, and diabetes mellitus ( 49 53 ). Ocular and neuro surgeries that affect the cornea such as cataract surgery, refractive surgery, keratoplasty, acoustic neuroma, trigeminal neuralgia, and neoplasms result clinically in NK by impairing trigeminal innervation on the surgical area ( 54 – 56 ). Six (40%) of our patients had previous ocular surgery with the majority having cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the different therapies of cerebral tumors such as surgery ( 19 – 22 ) radiotherapy, ( 23 ) and systemic chemotherapy ( 24 , 25 ) may also alter the nerve fibers or induce limbal stem cell deficiency ( 26 , 27 ) resulting clinically in NK.…”
Section: Discussionmentioning
confidence: 99%